METHODOLOGICAL INSTITUTIONALISM IN THE CONTEXT OF ECONOMIC SCIENCE EVOLUTION - Gligorijević, Nemanja J; Pavlović, Miloš LJ; Vujović, Tanja M (Collection of Papers of the Faculty of Philosophy in Priština, 2014)
As the achievements of modern civilization and a result of dominant trend of modern science, the existing methodological concepts of scientific progress analysis are incomplete and inadequate. Institutionalization of the science comes to redefining the hierarchy and heterarchies in the organization of scientific research, which raise the level of cognitive effects at the level of the individual to the collective level, leading to the establishment of a new relationship between the individual and the scientific and ideological institutions. Contradictions between cognitive status and interests of each of the agents (operatives scientific and ideological institutions) must be reflected in a scientific paper and thus the overall trend of progress in science. Rationality of an agent is a function compilation influence cognitive and institutional interests.